A política social e o conservadorismo econômico: O que revela o período recente - Luana Passos; Fernando Gaiger Silveira; Fabio Domingues Waltenberg (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– This text has two objectives that complement each other. First, to investigate the behavior of social policy and its consequences. Then to assess whether Brazilians became more conservative, despite the progress seen in social actions. As a methodology, a descriptive analysis of data from different sources is presented - National Household Sample Survey, Laboratory of Public Opinion in Latin America, Oxfam Brazil/Datafolha Institute - as well as a literature review on the 2013 protests. The results point to the progress of social policy with repercussions on the fall of poverty and inequality, however, with setbacks materializing in the Constitutional Amendment 95 and, in labor and social security reforms. Amid the inflection that started with the 2013 demonstrations, the available data on social preferences diverge, and it is not prudent to refute or corroborate the hypothesis of a wave of economic conservatism, although the election of a far-right government suggests a conservative attitude of society.
Keywords: I00; I30; I38; 330; social policy; 2013 demonstrations; social preferences; conservative wave